SHEEP FARMER'S RESPONSE TO COUNSELING ON CHATGPT UTILIZATION IN PURWABAKTI VILLAGE PAMIJAHAN DISTRICT BOGOR REGENCY - Haz, Hamzah; Purwanti, Maya; Suryanti, Reni (Jurnal Penyuluhan Pertanian, 2023)
Sheep farmers' knowledge of information technology is still low. This condition leads to low sheep productivity. The objectives are to find the responses of sheep farmers regarding the use of ChatGPT for searching information and analyze the influence of internal and external factors on the responses of sheep farmers, and formulate strategies to improve the response. The assessment design was one shot case study, with sampling technique using purposive sampling, with 30 respondents. The assessment will be carried out in Purwabakti Village, Pamijahan District from April to June 2023. Data processing used descriptive analysis to determine the response, multiple linear regression analysis to determine the influence of independent variables on farmer responses, and SWOT analysis to formulate strategies to improve farmer responses in Purwabakti Village. The results showed that sheep farmers in Purwabakti Village, had a good response about the used of ChatGPT for information search. Factors that influence farmers' responses include aged, non-formal education, raising livestock experienced, number of livestock ownership, quota expenditure, and internet access time. The strategy to increase farmers' response to search information with ChatGPT is to implement an aggressive strategy, namely by carrying out technology skills training and mentoring